2015
DOI: 10.18044/medinform.201521.86
|View full text |Cite
|
Sign up to set email alerts
|

Inosine Pranobex (Isoprinosine) – a Potential Adjuvant in the Management of Chronic HBV Infection

Abstract: After achieving a durable on-treatment virological response with NUC (nucleos(t)ide analogues), adding an immunomodulating agent seems to have beneficial effect on the course of chronic HBV disease. Methods: Nine patients were investigated (5 -HBeAg(-) and 4 -HBeAg(+). All patients achieved durable on-treatment virological response with NA and then Isoprinosine was added for a period of 21 to 27 months. Serum HBsAg and HBV DNA levels were evaluated at a 3-month interval. Aim: The aim of the present study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Our findings of survival or protection could be explained on the basis of the significant decrements of NDV titer in IAD only, Vaccine only and IAD + Vaccine groups comparing with control group indicated by PCR. Despite absence of similar findings in chickens, yet decreasing other virus titers by Isoprinosine may be supportive findings of the present study; for instance, [15] and [16] found that treatment with Isoprinosine decreased HB and HC virus titers, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings of survival or protection could be explained on the basis of the significant decrements of NDV titer in IAD only, Vaccine only and IAD + Vaccine groups comparing with control group indicated by PCR. Despite absence of similar findings in chickens, yet decreasing other virus titers by Isoprinosine may be supportive findings of the present study; for instance, [15] and [16] found that treatment with Isoprinosine decreased HB and HC virus titers, respectively.…”
Section: Discussionsupporting
confidence: 85%